Busca de variações nos genes MSX-1: relação com a hipodontia - Silva, Elisângela Ribeiro da (2007)
CHAPER I: Through a review of the literature, this article discusses the genetic mechanisms that control tooth morphogenesis. Emphasis is placed upon the structure and function of some key molecules that participate in interactions between its epithelial-mesenchimal components. In this paper we will can understand the mechanisms that control tooth morphogenesis and the dentistry should pay special attention to possible consequences of tooth number anomalies. CHAPER II: The analysis of DNA is widely employed in the genetic studies. Human DNA in most cases is performed with samples obtained from peripheral blood. The use of buccal epithelial cells as a source of DNA for PCR amplifications has several advantages over blood sampling. In the present study our objective was to standardize DNA extraction from an oral swab, using a simple method. To test DNA quality, we amplified the exons 2 of MSX1 gene and the promoter region of LEF1 gene to patients with hypodontia. In conclusion, we standardized a simple DNA. extraction of oral cells, which presented lower costs and faster results, indicating to that DNA from oral brushes/swabs are a reliable source for genetic studies. The quantity and quality of extracted DNA was shown to be adequate for PCR and polymorphism analyses. CHAPER III: Hypodontia, the congenital absence of one or a few teeth, is one of the most common alterations of the human dentition. The most common permanent missing teeth are the third molars, second premolars, and maxillary lateral incisors. Although hypodontia does not represent a serious public health problem, it may cause masticatory and speech dysfunctions and esthetic problems. In human the participation of MSX1 gene in craniofacial development have been evidenced by the studes that showed mutations in this gene. Hypodontia were shown to be caused by mutations in the MSX1 gene in human however, the mutation in the MSX1 gene cannot explain all types of tooth agenesis. Our data suggest that polymorphisms in MSX1 gene are associated with hypodontia.